The Influence of Social Capital in Table Banking On the Performance of Women-Owned Business Enterprises in Eldoret East Sub-County, Kenya - Jelagat, Oloibe; Phyllis Osodo, Owino (British Journal of Marketing Studies, 2016)
The study sought to understand the effects of table banking on performance of women-owned enterprises in Eldoret East Sub-County. Based on the study, this paper examines the extent to which social capital in table banking groups affects performance of women-owned enterprises. The study adopted a correlational research design with the target population being all women-owned enterprises in Eldoret East Sub-County from 2010 to 2014. A sample size of 384 respondents was obtained using Yomane formula of sample size. The study used multivariate linear Regression to establish the relationship between table baking and social capital and business performance indicators. Pearson product moment correlation(r) was applied to establish the relationship between the variables. From the findings of the research it was concluded that social capital has a strong positive effect on the business performance of women-owned enterprises. This is attributable to the fact that during meetings the members are able to discuss the challenges they face in running their businesses and how well they can improve their incomes. The study also established a positive correlation relationship between table banking and women-owned enterprises in Eldoret East Sub-County. It was, therefore, concluded that table banking has a positive influence on the business performance of women-owned enterprises in the area. The study recommends that women should be encouraged to form groups and register with the Ministry of Culture and Social Services.